Influence of protein tyrosine phosphatase gene (PTPN22) polymorphisms on rheumatic heart disease susceptibility in North Indian population. Issue 5 (2nd October 2014) - Gupta, U.; Mir, S. S.; Chauhan, T.; Garg, N.; Agarwal, S. K.; Pande, S.; Mittal, B.
<x xml:space="preserve">Abstract</x> This study was aimed to assess the association of Protein tyrosine phosphatase non‐receptor22 (PTPN22) gene single nucleotide polymorphisms (SNPs) with rheumatic heart disease (RHD) susceptibility in 400 RHD patients and 300 controls. The PTPN22 polymorphisms (rs2476601, rs1217406 and rs3789609) were genotyped using Taqman probes (Applied Biosystems, Foster City, CA). Statistical analysis was performed by spss and haplotype analysis by snpstat. The frequencies of variant alleles were not different between controls and cases (rs2476601: 2.00% & 1.05%; rs1217406: 36.33% & 34.75%; and rs3789609: 38.17% & 40.00%, respectively]. However, G rs2476601 A rs1217406 T rs3789609 haplotype turned out to be a low risk factor for RHD (P = 0.0042) predisposition in females and adult patients. This study suggests PTPN22 haplotype may modulate the risk to RHD in North Indians.